2004
DOI: 10.1111/j.0906-6705.2004.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of APAF‐1 expression in human cutaneous melanoma progression

Abstract: APAF-1 plays a pivotal role in mitochondria-dependent apoptosis, binding to cytochrome c and favoring activation of caspase-9. It has been shown that epigenetic silencing of the APAF-1 gene is a common event in several metastatic melanoma cells in vitro. We determined, by Western blot, variation in the level of expression of APAF-1 in several human melanoma cell lines and, by immunohistochemistry, in a group of 106 histological samples including benign and malignant melanocytic lesions. We observed APAF-1 down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 18 publications
5
45
0
2
Order By: Relevance
“…4,5 Moreover, our experiments correlating Apaf-1 expression with chemosensitivity were conducted blindlyone laboratory (YL) measured Apaf-1 expression and the other (SWL) assayed apoptosis and the results were compared later. Finally, we confirmed the immunoblotting results by Northern blotting and in situ hybridization 1 and, more recently, other investigators corroborated our observations using three different antibodies, [6][7][8][9] and by LOH analyses and quantitative RT-PCR. 10,11 Given that technical issues are unlikely to account for the differences between data sets, it is possible that the studies by Peltenburg and Allen did not examine enough samples to make reliable conclusions.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…4,5 Moreover, our experiments correlating Apaf-1 expression with chemosensitivity were conducted blindlyone laboratory (YL) measured Apaf-1 expression and the other (SWL) assayed apoptosis and the results were compared later. Finally, we confirmed the immunoblotting results by Northern blotting and in situ hybridization 1 and, more recently, other investigators corroborated our observations using three different antibodies, [6][7][8][9] and by LOH analyses and quantitative RT-PCR. 10,11 Given that technical issues are unlikely to account for the differences between data sets, it is possible that the studies by Peltenburg and Allen did not examine enough samples to make reliable conclusions.…”
supporting
confidence: 91%
“…11 Baldi et al, Dai et al, Zannon et al and Mustika et al report a heterogeneous expression of Apaf-1, highly positive in benign nevi but weak or undetectable in 35-50% in situ melanomas and lymph node and visceral metastases. [6][7][8][9] In addition, Qin et al have also independently reported low Apaf-1 expression in metastatic melanoma cell lines used in our initial study. 12 These results, along with recent reports of low Apaf-1 expression in other melanoma cell lines, 13 are consistent with our initial findings.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Contrarily, Baldi et al (2004) reported that reduced Apaf-1 expression correlated with melanoma thickness. The following reasons may result in the discrepancy between our results and those by Baldi et al: (1) different antibodies used for immunohistochemical staining; and (2) different technical approaches for immunohistochemisty.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39] This finding makes the Apaf1 yautja allele unique compared with existing targeted Apaf1 mutant alleles, which all lack protein expression. [18][19][20] We next examined the susceptibility of Apaf1 yautja MEFs to apoptotic stimuli.…”
Section: Resultsmentioning
confidence: 99%